2015
DOI: 10.1176/appi.ps.201300517
|View full text |Cite
|
Sign up to set email alerts
|

Provision of Mental Health Services as a Quality Indicator for Adolescent Substance Abuse Treatment Facilities

Abstract: Objective We sought to test whether adolescents receiving substance use treatment at facilities offering full (can treat all psychiatric conditions) or partial (do not treat severe/persistent mental illness) mental health services have better 12-month substance use and mental health outcomes. Methods Data was collected from 3,235 adolescents served at one of 50 adolescent treatment facilities who were assessed at baseline and at 12-months. Propensity scores were applied to compare client outcomes from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…heterogeneity between A-CRA and MET/CBT5, we used balancing weights (Hainmueller, 2012) to balance the two groups on 27 pretreatment variables that experts have been identified as important potential predictors of treatment assignment for adolescents and SUD (Grant et al, 2019) and that the literature has identified as key potential predictors of outcomes in this sample (Griffin et al, 2012;Griffin et al, 2014;Griffin et al, 2011;Ramchand, Griffin, Hunter, et al, 2014;Ramchand et al, 2011;Schuler et al, 2014). The full list of pretreatment characteristics used in this study are shown in Table 1.…”
Section: Pre-treatment Characteristics-to Adjust For Observed Pretreatmentmentioning
confidence: 99%
“…heterogeneity between A-CRA and MET/CBT5, we used balancing weights (Hainmueller, 2012) to balance the two groups on 27 pretreatment variables that experts have been identified as important potential predictors of treatment assignment for adolescents and SUD (Grant et al, 2019) and that the literature has identified as key potential predictors of outcomes in this sample (Griffin et al, 2012;Griffin et al, 2014;Griffin et al, 2011;Ramchand, Griffin, Hunter, et al, 2014;Ramchand et al, 2011;Schuler et al, 2014). The full list of pretreatment characteristics used in this study are shown in Table 1.…”
Section: Pre-treatment Characteristics-to Adjust For Observed Pretreatmentmentioning
confidence: 99%
“…In brief, they cover a range of baseline confounders including sociodemographic factors like age, race/ethnicity, and gender as well as baseline measures of substance use, mental health and environmental risk. These confounders were chosen based on prior research with experts in the field of SUD Grant et al (2020) as well as the literature as key potential predictors of outcomes in this sample Griffin et al (2012), Ramchand et al (2015), Ramchand et al (2014), Ramchand et al (2011), Schuler et al (2014. While dealing with variable selection for PS and outcome model is beyond the goal of this current tutorial Brookhart et al (2006), Hirano and Imbens (2001), we note that it is important to ensure selection of all important potential confounders prior to performing the analyses outlined in this tutorial.…”
Section: Study Datamentioning
confidence: 99%
“…For these patients, accessing treatment can be exceedingly difficult, as most mental health services are not commissioned to treat young people with SUDs and, conversely, most programmes for SUDs are not well prepared to treat mental disorders (Sterling 2010). Even when offered access to treatment services, young people with a dual diagnosis often struggle to engage with treatment, owing to their low motivation and poor insight (Ramchand 2015). This inevitably leads to further deterioration in their mental health and psychosocial functioning and increases the levels of tension and frustration within the family unit, as the patient may seem oblivious to dangers associated with continued substance use.…”
Section: Learning Objectivesmentioning
confidence: 99%